The reality and importance of medical and health monitoring for junior football players in first division professional teams - saadsaoud, Fouad (sports creativity, 2025)
Sports activity is considered a vital component of modern societies, encompassing health, intellectual, physical, and psychological aspects, thus making it of paramount importance in the policies of societies that aspire to promote practice and training as a cornerstone of modernity, a necessity to keep pace with developed nations. However, practicing any sport is subject to numerous conditions to ensure the participant's suitability, including undergoing various medical examinations that help avoid many errors that could lead to health complications negatively impacting the participant. The importance of medical monitoring is particularly evident among younger age groups who have never undergone medical examinations before. Such monitoring contributes significantly to facilitating the training process at all stages and under all types of conditions, which may sometimes appear to be highly strenuous. The child's body may respond to these conditions or exhibit negative reactions, leading to various injuries that occur on the sports field. All of this may stem from neglecting the specific developmental and physiological characteristics of this age group. Furthermore, the laws and regulations governing football in our country stipulate mandatory medical examinations for all athletes affiliated with various clubs. Article 13 of the regulations of the Algerian Football Federation mandates that every player undergo chest and cardiac examinations to be allowed to join a club and participate in competitions. However, it is noted that these tests remain insufficient as they are only conducted at the beginning of the season at most clubs, which makes them insufficient to monitor the player’s health status, and thus avoid all possible injuries at the beginning, during and end of the season.